Clinical outcome and side effects of concomitant chemoradiotherapy in the treatment of locally advanced inoperable non-small cell lung cancer: Our experiences - Radojičić Bojan; Radojičić Marija; Mišović Miroslav; Kostić Dejan (Vojnosanitetski Pregled)
Background/Aim. About 1.8 million new lung cancer cases are diagnosed worldwide every year, and about 1.6 million cases have a fatal outcome. Despite improvements in treatment in the previous decades, the survival of patients with lung cancer is still poor. The five-year survival rate is about 50% for patients with localized disease, 20% for patients with regionally advanced disease, 2% for patients with metastatic disease, and about 14% for all stages. The median survival of patients with untreated non-small cell lung carcinoma (NSCLC) in the advanced stage is four to five months, and the annual survival rate is only 10%. The aim of the study was to determine the results of treatment with concomitant chemoradiotherapy (CHRT) in terms of efficacy and toxicity in selected patients with advanced inoperable NSCLC. Methods. The study included data analysis of 31 patients of both sexes who were diagnosed and histopathologically verified with NSCLC in inoperable stage III and were referred by the Council for Malignant Lung Diseases to the Radiotherapy Department of the Military Medical Academy in Belgrade, Serbia for concomitant CHRT treatment. Upon expiry of the three months from the performed radiation treatment (RT), the tumor resonance was assessed based on multislice computed tomography (MSCT) examination of the chest and upper abdomen according to Response Evaluation Criteria in Solid Tumors (RECIST) version 1.1. According to the same criteria, progression-free survival (PFS), as well as overall survival (OS), was assessed every three months during the first two years, then every 6 months or until the onset of disease symptoms. Results. The median PFS was 13 months, and the median OS was 20 months. During and immediately after RT, 9 (29%) patients had a grade 2 or higher adverse events. Conclusion. The use of concomitant CHRT in patients in the third stage of locally advanced inoperable NSCLC provides a good opportunity for a favorable therapeutic outcome with an acceptable degree of acute and late toxicity and represents the standard therapeutic approach for selected patients in this stage of the disease.